PENGARUH SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA INSTANSI PEMERINTAH KOTA SAMARINDA (Studi Satuan Kerja Perangkat Daerah Kota Samarinda) - Amiruddin Amiruddin; Omar Dhanny; Rafika Rafika (Jurnal Eksis, 2019)
This research aims to test (1) The influence of information systems accounting towards the performance of government agencies. (2) Effect of internal control on the performance of government agencies. This research was conducted in Samarinda. This research uses a quantitative research type. The data source in this study is using primary data of questionnaires. The population in this study was SKPD Samarinda City. The sample on this study was 168 people. Data is used and analyzed multiple linear regression with assisted statistical programs (SPSS version 15). The results of the hypothesis testing showed that the X1 accounting information system did not significantly influence the performance of the government agency of Samarinda. While internal control system variables X2 significantly affected the performance of the government agency of Samarinda. In the study, it can also be learned that the accounting information system and internal control system have a simultaneous effect on the performance of government agencies as variable (Y). The most dominant Data contained in the variable (X2) is the internal control system. Because the internal control system is able to provide effective and efficient supervision.  Keywords: Accounting Information System, Internal Control System and Government